Education For All (EFA): A Focus on Public Primary Schools’ Facilities, Curriculum and Teachers’ Professional Development in Lagos and Ogun States, Nigeria - Ige, Olumide Olakunle; Omotuyole, Christy Owolemi; Sebili, Olabisi Toyyibah (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
Although Education for All (EFA) was adopted over two decades ago by the signatory nations of the UN, it is evident that some nations, including Nigeria, are still struggling to accept its underlining requirement for its implementation. This study focused on the implementation of Education for All (EFA) in public primary schools in Lagos and Ogun States with regard to their facilities, curriculum and teachers’ professional development. Three research questions were raised and answered. The study adopted descriptive survey design. The study involved a total of 40 public primary schools, 400 teachers and 10 Basic 3 classrooms selected from Lagos and Ogun states in Nigeria. Data were gathered by means of teachers’ questionnaire and checklist for early childhood education. Data collated were analyzed using percentages, arithmetic mean and standard deviation. The study found that: While basic facilities are either fairly or adequately available in public primary schools in both states,, facilities for inclusive education are either inadequate or completely unavailable; The specified school curricula in the two states are not adequate in terms of procedure, instructional materials, methods and non-discriminatory strategies; and, Governments of both states do not engage public primary school teachers in continuous professional development. The study concluded that the operation of public primary schools presently falls short of expectations of EFA framework of actions. Recommendations are made on the basis of the findings of the study. Keywords: Education for All, Early Childhood Education, Inclusive Education